2009
DOI: 10.1007/s11661-009-9986-y
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Growth Transport in Oxide Scales on Fe-16Cr Steels in Water Vapor

Abstract: The oxidation behavior of Fe-16Cr steels in N 2 -12 vol pct H 2 O was studied at 850°C. The oxide scale was compact and had excellent adhesion to the substrate; moreover, there were three layers of different compositions existing in the scale. To gain an insight into the transport mechanism, two-stage oxidation was carried out in N 2 -12 vol pct H 2 16 O and followed in N 2 -12 vol pct H 2 18 O gas mixtures. The oxygen isotope profiles in oxide scales were determined by secondary ion mass spectrometry. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…45,46 Isotopic tracer studies have been widely used in oxidation studies of Al-, Fe-, Ni-, and Zr-base alloys, as well as SiC, with significant new insights gained regarding the growth mechanism of the oxide films. 45,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] However, application of this experimental approach to Mg is particularly challenging due to the formation of both MgO and Mg(OH) 2 products in the film, necessitating the use of both 16 O/ 18 O and H/D tracer species. Furthermore, the corrosion films formed on Mg are frequently heterogeneous and non-uniform, and can involve multiple mechanisms, including Mg dissolution, solid-state MgO or Mg(OH) 2 film growth, and precipitation of Mg(OH) 2 from solution to the film surface.…”
mentioning
confidence: 99%
“…45,46 Isotopic tracer studies have been widely used in oxidation studies of Al-, Fe-, Ni-, and Zr-base alloys, as well as SiC, with significant new insights gained regarding the growth mechanism of the oxide films. 45,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] However, application of this experimental approach to Mg is particularly challenging due to the formation of both MgO and Mg(OH) 2 products in the film, necessitating the use of both 16 O/ 18 O and H/D tracer species. Furthermore, the corrosion films formed on Mg are frequently heterogeneous and non-uniform, and can involve multiple mechanisms, including Mg dissolution, solid-state MgO or Mg(OH) 2 film growth, and precipitation of Mg(OH) 2 from solution to the film surface.…”
mentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Such insights have proven particularly useful for understanding the influence of various alloying additions on film growth, and provide a basis for improved alloy design. For example, tracer studies of Al 2 O 3 -forming alloys with and without rare earth element dopants revealed beneficial effects related to more protective, oxygen inward growth mechanisms [e.g.…”
mentioning
confidence: 99%
“…Isotopic tracer studies have been widely applied to studies of the high-temperature oxidation of alloys (Al, Fe, Ni, and Zr base; SiC), with significant new insights gained regarding the growth mechanism of the oxide films. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Such insights have proven particularly useful for understanding the influence of various alloying additions on film growth, and provide a basis for improved alloy design. For example, tracer studies of Al 2 O 3 -forming alloys with and without rare earth element dopants revealed beneficial effects related to more protective, oxygen inward growth mechanisms [e.g.…”
mentioning
confidence: 99%